2023
DOI: 10.3390/nu15092017
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cariogenic Properties of Lactobacillus plantarum in the Utilization of Galacto-Oligosaccharide

Abstract: Ecological approaches can help to correct oral microbial dysbiosis and drive the advent and persistence of a symbiotic oral microbiome, which benefits long-term dental caries control. The aim of this study was to investigate the impact of the prebiotic Galacto-oligosaccharide (GOS) on the growth of probiotics L. plantarum 14,917 and its effect on the inhibitory ability of L. plantarum 14,917 against the growth of Streptococcus mutans and Candida albicans in an in vitro model. Single-species growth screenings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…NETs were pre-incubated at 37°C, and diluted with sterile PBS. Gradient-diluted NETs were dispensed into 96-well plates, and C. albicans (1×10³ CFUs ( 54 , 55 )) or S. aureus (1×10 6 CFUs ( 56 )) were added, separately or combined. After incubation at 37°C for 2, 4, and 8 h, samples were collected, diluted, plated, and CFU counts were performed.…”
Section: Methodsmentioning
confidence: 99%
“…NETs were pre-incubated at 37°C, and diluted with sterile PBS. Gradient-diluted NETs were dispensed into 96-well plates, and C. albicans (1×10³ CFUs ( 54 , 55 )) or S. aureus (1×10 6 CFUs ( 56 )) were added, separately or combined. After incubation at 37°C for 2, 4, and 8 h, samples were collected, diluted, plated, and CFU counts were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the standard curves for these three strains, when morning starters reached the target OD, the represented concentration of C. albicans was 10 6 CFU/mL, S. mutans was 10 8 CFU/mL, and L. plantarum was 10 9 CFU/mL. The morning starters were then serial dilution into starting concentration for the planktonic models described below [ 28 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sugar substitutes can indeed serve as an alternative to sucrose helping to reduce the risk of caries. In the recent study, Galacto-oligosaccharide (GOS), a low-calorie sweetener, has been found to suppress the hyphal formation of C. albicans and the acid resistance of the C. albicans-S. mutans interaction [ 81 ]. The finding suggests that sugar substitutes may have potential in inhibiting the growth and virulence of C. albicans and its cooperation with S. mutans, which could contribute to the prevention of caries.…”
Section: The Influence Of External Factors On Oral Microbiomesmentioning
confidence: 99%